CALCULATION OF THE LATERAL FACE PROFILE OF SPRING INGOT AND ITS INFLUENCE ON THE SIZE OF WIDENING - L. A. Isajevich; A. G. Gerasimova; M. I. Sidorenko (Литьë и металлургия, 2004)
There are given the results of theoretical and experimental investigations on determination of actual value of widening and the side surfase line of end sections of spring ingot of variable thickness to auxiliaries. There is shown up that, it is possible to change the geometry of the bar side line after rolling, modifying by the parameters of the initial side line of bar.